Institutional innovations in African smallholder carbon projects - Shames, Seth; Wollenberg, Eva Karoline; Buck, Louise E.; Kristjanson, Patricia M.; Masiga, Moses; Biryahwaho, B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
This paper synthesizes the insights of six African agricultural carbon project case studies and identifies institutional innovations among these projects that are contributing to long-term project success while maximizing benefits and minimizing risk for participating farmers. We review project organization and management, the structure and role of community groups within the projects, costs and benefits for managers and farmers, strategies to manage risks to farmers, and efforts to support women’s participation. Projects have developed organizational systems for financial management, agricultural extension, and carbon monitoring. All of these were managed by project management entities, with farmers implementing practices and supporting monitoring systems. Most projects engaged farmers in small groups and larger clusters of groups, which enabled broad participation, efficient contracting, timely communication, provision of extension services, benefit-sharing, and gender-focused activities. Direct carbon payments to farmers were low. Consequently projects needed to manage expectations around benefits carefully, support more efficient systems of aggregation and ensure non-cash benefits for farmers. Managing power dynamics within and among farmer groups was a significant challenge to ensuring equitable decision-making and participation. Mechanisms for settling conflict over land and benefits were also critical. We present action research questions that emerged from the first phase of this work and discuss the future of the initiative. Case studies about each agriculture carbon project from which our analysis is drawn can be downloaded along with the main report.